2019
DOI: 10.1088/1755-1315/386/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Application of a neural network model to forecasting of El Niño and La Niña

Abstract: In this paper, a possibility to forecast El Niño and La Niña by using an artificial intelligence model based on neural networks is studied. The quality of such a long-term climate forecast is assessed too. A set of global climatic indices of atmosphere-ocean system oscillations in 1950-2019 is used as input parameters of the model. The Nino3.4 index is calculated by using monthly average 500mb geopotential height and sea surface temperature fields from NCEP/NCAR reanalysis data sets. A verification of the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…Other similar works include a standard neural network applied by Lubkov et al [42] to forecast El Niño and La Niña based on a set of global climatic indices of atmosphere-ocean system oscillations, with a lead time of 3 months. Petersik and Dijkstra [43] applied Gaussian density neural network and quantile regression neural network to forecast ONI, for lead times of up to 21 months.…”
Section: Related Workmentioning
confidence: 99%
“…Other similar works include a standard neural network applied by Lubkov et al [42] to forecast El Niño and La Niña based on a set of global climatic indices of atmosphere-ocean system oscillations, with a lead time of 3 months. Petersik and Dijkstra [43] applied Gaussian density neural network and quantile regression neural network to forecast ONI, for lead times of up to 21 months.…”
Section: Related Workmentioning
confidence: 99%
“…The adaptation of the model was carried out by analogy with the paper [61] and included the stages of preprocessing, modeling and postprocessing. At the stage of preliminary data processing, a search was made for the correlation relationships between the frequency of intense cyclones and the values of the indices of large-scale signals in the previous 2, 4 and 6 months, after that the input parameters having the greatest relationship with the prognostic parameter were selected for the model operational work.…”
Section: Neural Network Modelmentioning
confidence: 99%
“…For instance, [21] found that the application of a neural network to create a nonlinear PCA approach was successful in extracting periodic modes in the tropical Pacific. References [22][23][24][25] used convolutional neural networks to forecast the time amplitude and type of ENSO. Labe and Barnes [26] applied ANN to predict the onset of slowdowns in decadal warming trends of global mean surface temperature.…”
Section: Introductionmentioning
confidence: 99%